2006
DOI: 10.1016/j.immuni.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Vesicles Crossprime CD8 T Cells and Protect against Tuberculosis

Abstract: CD8 T lymphocytes are important effectors in protective immunity against Mycobacterium tuberculosis. We recently characterized the detour pathway of CD8 T cell activation in tuberculosis mediated by apoptotic vesicles from infected cells that transport mycobacterial antigens to dendritic cells (DCs). Here we demonstrate that apoptotic vesicles from mycobacteria-infected macrophages stimulate CD8 T cells in vivo. Homing of DCs to draining lymph nodes was critically required for effective crosspriming. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
314
1
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(338 citation statements)
references
References 53 publications
10
314
1
6
Order By: Relevance
“…Among them were genes of the Bcl-2 family (Bcl-3 and Bcl-6), and genes of the Fas and TRAIL pathways. The importance of apoptosis and its manipulation by M.tb becomes increasingly evident [80,81]. Moreover, H37Rv, but not H37Ra, inhibits apoptosis in vitro [82] and causes exacerbated necrosis in Mf in vitro [83].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Among them were genes of the Bcl-2 family (Bcl-3 and Bcl-6), and genes of the Fas and TRAIL pathways. The importance of apoptosis and its manipulation by M.tb becomes increasingly evident [80,81]. Moreover, H37Rv, but not H37Ra, inhibits apoptosis in vitro [82] and causes exacerbated necrosis in Mf in vitro [83].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…In mice depleted of DCs, dying tumor cells fail to elicit anticancer immune responses. 29,34,35 The prevailing model for cross-presentation of tumor antigen by DC relies on a three-step process, where DC are central ( Figure 1). First tumor cells are killed, second DC undergo activation and maturation, third tumor antigen is presented by DC to T cells.…”
Section: Cell Death and The Link Between Innate And Acquired Immunitymentioning
confidence: 99%
“…In the case of mycobacteria, it has been demonstrated that apoptotic vesicles from infected cells containing antigens of the bacillus associated with MHC class I can specifically stimulate CD8+ T cells. (5) Alternatively, in a phenomenon known as cross-presentation, antigens of intracellular pathogens can directly access the presentation via MHC class I cells, owing to the capacity of the phagosomes to fuse with the endoplasmic reticulum, and to the protein recruitment from the endoplasmic reticulum to the phagosome. Consequently, phagocytosed antigens can access the cytoplasm, suffer degradation by proteases, known as proteasomes, return to the phagosome through transporters associated with antigen processing (TAPs), and bind to MHC class I molecules located in the phagosome, leading to the subsequent expression on the cell surface and to the recognition by CD8 + cells.…”
Section: Immune Response To M Tuberculosismentioning
confidence: 99%